Improving the communication reliability of body sensor networks based on the IEEE 802.15.4 protocol - Gomes, Diogo (2014)
Body sensor networks (BSNs) enable continuous monitoring of patients anywhere, with minimum constraints to daily life activities. Although the IEEE 802.15.4 and ZigBee® (ZigBee Alliance, San Ramon, CA) standards were mainly developed for use in wireless sensors network (WSN) applications, they are also widely used in BSN applications because of device characteristics such as low power, low cost, and small form factor. However, compared with WSNs, BSNs present some very distinctive characteristics in terms of traffic and mobility patterns, heterogeneity of the nodes, and quality of service requirements. This article evaluates the suitability of the carrier sense multiple access–collision avoidance protocol, used by the IEEE 802.15.4 and ZigBee standards, for data-intensive BSN applications, through the execution of experimental tests in different evaluation scenarios, in order to take into account the effects of contention, clock drift, and hidden nodes on the communication reliability. Results show that the delivery ratio may decrease substantially during transitory periods, which can last for several minutes, to a minimum of 90% with retransmissions and 13% without retransmissions. This article also proposes and evaluates the performance of the BSN contention avoidance mechanism, which was designed to solve the identified reliability problems. This mechanism was able to restore the delivery ratio to 100% even in the scenario without retransmissions.